Strategic Extremism: Why Republicans and Democrats Divide on Religious Values - Glaeser, E. L.; Ponzetto, G. A. M.; Shapiro, J. M. (Quarterly Journal of Economics, 2005)
Party platforms differ sharply from one another, especially on issues with religious content, such as abortion or gay marriage. Given the high return to attracting the median voter, why do vote-maximizing politicians take extreme positions? In this paper we find that strategic extremism depends on an intensive margin where politicians want to induce their core constituents to vote (or make donations) and the ability to target political messages toward those core constituents. Our model predicts that the political relevance of religious issues is highest when around one-half of the voting population attends church regularly. Using data from across the world and within the United States, we indeed find a nonmonotonic relationship between religious extremism and religious attendance.